PERANCANGAN SISTEM MONITORING DAN KONTROL KUALITAS AIR SERTA PEMBERIAN PAKAN OTOMATIS PADA BUDIDAYA LELE BIOFLOK BERBASIS INTERNET OF THINGS - Dendy Denhero, Gde; Elba Duta Nugraha, I Putu; Jasa, Lie (Jurnal SPEKTRUM, 2022)
Cultivation with a biofloc system has several advantages and disadvantages. Biofloc catfish cultivation technology is a technique to balance carbon and nitrogen levels in water to improve pond water quality. However, cultivators must make observations in the cultivation pond water more often and carefully in order to prevent the increase in nitrogen levels. So, referring to this, a monitoring and control system for water quality and automatic feeding on biofloc catfish cultivation was designed. The research was conducted by applying the experimental method, in which the system is divided into three subsystems, namely water quality monitoring, automatic water replacement, and automatic feeding. The results obtained from conducting this research are in the form of tool trial data which will then be compared with data from the program that has been made, as well as performance data from the automatic water replacement subsystem and automatic feeding subsystem which were carried out for 5 consecutive days. The conclusion of this research is that the design of a water quality monitoring and control system and automatic feeding on biofloc catfish cultivation based on the Internet of Things has been successfully made. In the automatic water replacement subsystem, the average relative error is 2.75%. In the automatic feeding subsystem, the average difference in feeding time is 14.5 seconds and the average relative error is 3.3%.